The patient’s point of view: COVID-19 and neuroendocrine tumor disease - Krug, Sebastian; Khosravian, Maryam; Weissbach, Julia; George, Katharina; Damm, Marko; Garbe, Jakob; Walldorf, Jens; Reuken, Philipp Alexander; Amin, Tania; Siebenhüner, Alexander; Rosendahl, Jonas; Gress, Thomas Mathias; et al. (Cancers, 2022)
NET; neuroendocrine; COVID-19; SARS-CoV-2; survey; vaccination; anxiety; worries; psychological factors